ASPECTE STRATEGICE ALE AUTOREGLĂRII ÎNVĂŢĂRII ÎN MEDIUL ACADEMIC UNIVERSITAR - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2008)
Self-regulated learning strategies consist of cognitive and meta-cognitive activities, resource management activities, and affective activities (Zimmerman, Martinez, 1986; Pintrich, 1999). The purpose of this study was to investigate (1) if the use of self-regulated learning strategies was significantly related to academic performance, and than (2) compared for differences in the use of self-regulated learning strategies two groups: high level performance students (group A) and low level performance students (group B).